Technical assessment of an equatorial Low Earth orbit satellite constellation for Egypt - Haitham Akah; Dalia Elfiky (Egyptian Journal of Remote Sensing and Space Sciences, 2022)
Egypt, the region’s agricultural powerhouse, has the largest irrigation area among the eleven Nile Basin countries. Meanwhile, the demand for water and irrigation management is becoming necessary. The Internet of Things (IoT) plays a key role in smart agriculture and water management to cope with modern water scarcity. This paper presents the methodology of design and assessment of a small IoT satellite constellation providing continuous coverage over Egypt and decides on the optimal location for ground stations to serve IoT sector in Egypt. Moreover, it evaluates the latency analysis and handover time for such constellation.It is shown that a constellation of 9 satellites in a circular equatorial Low Earth Orbit (LEO) can provide continuous coverage for Egypt. The latency analysis showed that two ground stations in southernmost Egypt will provide the optimal latency for such constellation.